Distinctive association of peripheral immune cell phenotypes with capillaroscopic microvascular patterns in systemic sclerosis. (23rd June 2019) - Kubo, Satoshi; Nakayamada, Shingo; Miyazaki, Yusuke; Yoshikawa, Maiko; Yoshinari, Hiroko; Satoh, Yurie; Todoroki, Yasuyuki; Nakano, Kazuhisa; Satoh, Minoru; Smith, Vanessa; Cutolo, Maurizio; Tanaka, Yoshiya
Abstract: Objective: The pathological changes in SSc include immune system dysregulation and microvascular damage. However, the association of immune cell phenotype heterogeneity and microvascular abnormalities is unclear. The aim of this study is to elucidate this association in SSc. Methods: Peripheral blood mononuclear cells obtained from 150 SSc patients were used for comprehensive flow cytometric analysis based on the Human Immunology Project. Hierarchical cluster analysis was used to classify SSc patients into subgroups and their association with microvascular abnormalities, as assessed by nailfold videocapillaroscopy (i.e. 'early', 'active' and 'late' patterns), was analysed. Results: The proportions of activated CD4 + T cells, T cells re-expressing CD45RA, activated Th1 and Th17 cells and IgD − CD27 − B cells were higher in SSc patients than in healthy individuals. Hierarchical cluster analysis stratified SSc patients into three groups: patients with few immune abnormalities (fewer abnormalities group), patients with high proportions of activated T and Treg cells (Treg-dominant group) and patients with high proportions of Tfh and plasmablasts (Tfh-dominant group). Age and disease duration were comparable among the groups. On the other hand, microvascular abnormalities, especially the 'late' nailfold videocapillaroscopy pattern, correlated with internal organ involvement. Among the groups stratified according to immune cell phenotype, the progression to the 'late' nailfold videocapillaroscopy pattern was more frequent in the Tfh-dominant group. Conclusion: Our study confirmed the presence of immunophenotypic abnormalities in SSc. Immunological abnormalities were not uniform but rather limited to subpopulations, particularly the Tfh-dominant group, where they were highly associated with microvascular abnormalities and organ involvement.